The Readability Of Written Mass Mailing Material Produced At The County Level Of The Alabama Cooperative Extension Service - Earl C. Johnson; Satish Verma (Journal of Applied Communications, 1992)
Alabama county Extension agents' circular letters and newsletters (2.5 million pieces in 1998) were found to be two grade levels higher than the reading level of the average U.S adult, and 85 percent of Alabama 4-Hers.